Emergency department presentations in infants: Predictors from an Australian birth cohort. (25th July 2017) - Crilly, Julia; Cameron, Cate M; Scuffham, Paul A; Good, Norm; Scott, Rani; Mihala, Gabor; Sweeny, Amy; Keijzers, Gerben
Abstract : Aim: Infants under 12 months of age are disproportionately represented amongst emergency department (ED) presentations, and infants are more likely to be frequent ED users. This study aimed to describe and identify psychosocial predictors of ED presentation in infants. Methods: A prospective birth cohort from Queensland and New South Wales (Environments for Healthy Living) was used to understand infant health service use. Baseline and 12‐month questionnaire data pertaining to children born between 2006 and 2011 were used to identify predictors of ED presentation, using multiple regression analysis. Results: Of the 2184 children in the cohort with available baseline and 12‐month data, 579 (27%) presented at least once to an ED during their first 12 months of life. Statistically significant predictors of ED presentation in the multivariate analysis included the mother having asthma (odds ratio (OR) 1.67, 95% confidence interval (CI) 1.15–2.39) and a higher Kessler‐6 score (a measure of psychological distress) of the primary carer at baseline (OR 1.04, 95% CI 1.01–1.08). Maternal education level was not associated with ED presentations of infants. Conclusions: This study describes maternal and child factors of children who present to the ED in the first year of life. Factors related to an infant's support system were found to be predictors for an ED presentation in the first year of life. This study emphasises the need to review the maternal medical history and psychosocial situation. There may be benefits for health‐care practitioners to take the opportunity (such as during routine childhood immunisation) to perform a brief screening tool (such as the Kessler‐6) to understand psychological distress experienced by mothers. This may influence the likelihood of a child presenting to an ED within the first 12 months of life.